Site-dependent seismic response of high-rise buildings to long-distance earthquakes - Lu, Qiurong. (2008)
Linear elastic seismic response of two commercial buildings and two residential buildings in Singapore are carried out using the ETABS computer program. The commercial buildings are 18- (Building A) and 35-storey (Building B) high, while the residential buildings are 15- (Building C) and 25-storey (Building D) high. Building C is a medium-rise narrow rectangular block building, its longitudinal direction x-direction, and its transverse (short) direction y-direction. Building D is a high-rise square block building. The four buildings are first analysed as bare frames without the stiffness of masonry in-fill walls. The two residential buildings are then analysed considering the stiffness of masonry in-fill walls. In two horizontal orthogonal directions, the buildings are subjected to the tentative design response spectra that have been previously developed to represent the ground motion characteristics of rock, soil and soft soil sites in Singapore. In addition, the 2-D soil-structure interaction (SSI) and pile-soil-structure interation (PSSI) models of the 15-storey residential building are analysed by using ABAQUS software. The stiffness of masonry in-fill walls is first ignored and then included in the SSI and PSSI models.